Heart rate and cardiac conductivity disorders in junior athletes - Epishev, V. V.; Korableva, Y. B.; Bakushin, A. A.; Vedernikova, O. B. (Theory and Practice of Physical Culture, 2019)
The study topic is in high priority at present due to the reported growth of the heart rate disorders in athletes and the still limited knowledge of the reasons for the HR disorders. Objective of the study was to analyze the ECG variations in junior athletes competing in different sport disciplines. Sampled and tested in 2015 through 2018 at the Scientific Research Center were the 16-18 year-old male athletes (n=302) representing different sports. The test data were mined by Bruce Treadmill Test using SCHILLER Cardiovit AT-104 test system, and processed by Statistica 10.0 software toolkit. The sample was diagnosed with the HR and cardiac conductivity disorders including incomplete right bundle-branch block (IRBBB) (39.55% of the sample); extrasystoles (26.85 %); early repolarization syndrome (ERS) (20.89%), sinoatrial (SA) block (9.69%); and wandering pacemaker (2,99 %). The study data and analysis give us the grounds to conclude that the HR disorders are occasional i.e. non-associated with serious pathologies in anamnesis (manifested in short-term faints, syncope conditions, weakness, faintness etc.). It should be mentioned that the HR and cardiac conductivity disorders were not diagnosed in the intensive exercise tests. Therefore, the HR and cardiac conductivity disorders in the sample may be ranked with the functional versions of the sport form and, hence, shall not result in any limitations in the training process i.e. viewed as non-malignant developments showing no indications of regress towards unhealthy conditions.